Surface sterilization and shoot proliferation from shoot tip explant of cat's whiskers (Orthosiphon stamineus) using different concentration of Clorox and BAP - Borhan, Nur Hayyu (2016)
Orthosiphon stamineus which belongs to the Lamiaceae family is an important herb. A study was conducted to determine the best sterilization procedure for in vitro culture of Orthosiphon stamineus using shoot tip explant. Different concentrations of Clorox at different immersion time were used to optimize the sterilization procedure. Immersion of shoot tip explant in 25% concentration of Clorox for 15 minutes reduced microbial contamination up to 10% but increase explant survivability. Another study was conducted by culturing the shoot tip of Orthosiphon stamineus in half strength MS media containing different BAP concentration. The media containing 1 mg/L of BAP gave the highest shoot proliferation in shoot tip culture of Orthosiphon stamineus with 12.3 shoot produced per explant.